Creative people and places – an experiment in place-based funding. (1st October 2017) - Jancovich, Leila
There is a long-standing tradition in cultural policy of measuring the numbers of people who take part in subsidized arts practices. The data collected have informed strategies to remove individual barriers to participation, such as price, access or education. But researchers have increasingly challenged the deficit approach that defines non-participation as a 'problem', which rests with those not participating rather than with how the cultural sector operates. This article draws on the growing body of research that has shown how inequalities in participation relate to inequalities within the cultural sector itself, with a narrow range of people working in and defining what culture is valued, for the rest. It examines the concept of place-based funding as a lens through which to consider cultural provision and participation from an asset-based approach to understanding local specificity. Its focus is on Creative People and Places (CPP): an action research programme, in which Arts Council England targeted investment into local districts that were defined by a population survey as having low levels of arts participation. What the research demonstrates are the tensions inherent in national policy-makers' responses to local cultural needs. It considers the relationship between policy and implementation through consideration of the different governance models operating in the different places and argues for increased accountability of the cultural sector through participatory governance at a local level.